2009
DOI: 10.1021/ef900386x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Polar Species in Aviation Fuels using Multidimensional Gas Chromatography-Time of Flight Mass Spectrometry

Abstract: Aviation fuel is so complex that it is virtually impossible to separate all of the major components of the mixture, much less the minor components. The minor components are typically separated from the major components using preparative techniques (such as solid phase extraction;SPE) and then re-examined by gas chromatography-mass spectrometry (GC-MS). Without SPE, GC-MS is not capable of a comprehensive determination of the trace polar components in jet fuel due to fuel complexity. In this contribution, jet f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 14 publications
1
48
0
1
Order By: Relevance
“…GC × GC allows the utilization of several detectors, with few modifications to adapt them to the low volume and high velocity of data processing. One can be highlight the flame ionization detector (FID), time-of-flight mass spectrometry (TOF-MS) and quadrupole mass spectrometry (qMS) as the more used [197][198][199][200][201][202][203].…”
Section: Comprehensive Two-dimensional Gas Chromatography (Gc × Gc)mentioning
confidence: 99%
“…GC × GC allows the utilization of several detectors, with few modifications to adapt them to the low volume and high velocity of data processing. One can be highlight the flame ionization detector (FID), time-of-flight mass spectrometry (TOF-MS) and quadrupole mass spectrometry (qMS) as the more used [197][198][199][200][201][202][203].…”
Section: Comprehensive Two-dimensional Gas Chromatography (Gc × Gc)mentioning
confidence: 99%
“…Testing of the second wave of JP-8+100 additives is still underway ( This portfolio also included extensive modeling and trace species assessment in jet fuels , e.g. [2]. These measurements are necessary for accurate thermal stability modeling, which is often controlled by trace species concentration in jet fuel.…”
Section: ) Thermal Stability/thermal Managementmentioning
confidence: 99%
“…Table 1. Classification of compounds using MDGC-TOFMS analysis compared to total HPLC polars analysis [2]. Table 2.…”
Section: ) Thermal Stability/thermal Managementmentioning
confidence: 99%
“…More recently, Striebich et al [22] reported use of a system not unlike the one used in the previous work, incorporating a timeof-flight MS for aviation fuel analysis. A trapping interval of 15 s was employed, that was claimed to be about the duration of one peak width.…”
Section: Introductionmentioning
confidence: 99%